P75 A cost-effectiveness analysis of improving access to psychological therapies in british sign language (bsl). (2nd September 2017) - Shields, GE; Rogers, KD; Young, A; Buck, D; Davies, LM
Abstract : Background: Deaf BSL users can access standard Improving Access to Psychological Therapies (standard-IAPT) services with/without interpreter assistance in the UK. Some areas use specialist BSL-IAPT services, delivered by qualified IAPT workers who are fluent in BSL, addressing cultural and linguistic needs of Deaf users. This NIHR HS and DR funded study (Ref: 12/136/79) assessed the cost-effectiveness of BSL-IAPT, versus standard-IAPT services, for Deaf BSL users. Methods: A combined decision tree (initial IAPT intervention period) and Markov model (longer-term costs and health benefits) used a NHS and social care perspective to estimate the incremental cost/quality-adjusted life-year (QALY) gained and probability that BSL-IAPT is cost-effective. The probability of cost-effectiveness was estimated for willingness to pay thresholds from £0 to £30 000 to gain one QALY. The model structure was developed from published literature and extensive discussion with the research team and advisory group. Both included Deaf people. Data sources for clinical effectiveness, direct costs and utilities included systematic reviews, IAPT databases and new studies with Deaf BSL users. The timeframe was 5 years with costs and QALYs discounted. Probabilistic and deterministic sensitivity analyses assessed parameter and structural uncertainty. Results: BSL-IAPT is associated with a net saving of £240 (95th percentiles £2, 303, £935) and little difference in QALYs (net QALY 0.001; 95th percentiles −0.009, 0.013). In both cases the 95th percentiles cross zero, indicating uncertainty about the results. However, cost-effectiveness acceptability analysis indicated probability above 50% that BSL-IAPT is cost effective, even if decision makers are not prepared to pay to gain one QALY. Most sensitivity analyses also indicated that BSL-IAPT was likely to be cost effective. Exceptions were if it was assumed that (i) there was no additional cost for interpreters in Standard-IAPT cost; (ii) BSL-IAPT provides more high intensity care than currently, though the latter is very uncertain due to limited data. Conclusion: The primary analysis indicated that BSL-IAPT may be more cost effective than Standard IAPT. Limited data and reliance on a small sample of IAPT data means that the robustness of the results are uncertain. Nevertheless, this is the first economic evaluation of a healthcare for depression and anxiety interventions for Deaf BSL users. It provides initial information to support healthcare commissioners achieve increased access to effective and efficient psychological therapies for depression in Deaf people. The study also highlights the need for new research to prospectively collect robust data.